2021
DOI: 10.3390/life11121314
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction and Atopic Dermatitis: A Systematic Review

Abstract: Atopic dermatitis (AD) is a chronic inflammatory disease of the skin whose main symptom is pruritus and may affect all age ranges. Regarding the prevalence, it has been estimated at around 10% of the world population. Many concomitant diseases have been associated with AD, but the causal relationship between AD and psychological impairment has not been clearly established. Scientific literature studying the probable association between male or female sexual dysfunction and dermatological pathology is limited, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Somewhat surprisingly, the situation with genital herpes was reversed: patients with severe AD had significantly fewer genital HSV symptoms. We hypothesize that this could be explained by sexual dysfunction associated with severe AD (25), leading to a smaller number of sexual partners. This hypothesis is, however, challenged by the opposite finding regarding the risk of condylomas.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat surprisingly, the situation with genital herpes was reversed: patients with severe AD had significantly fewer genital HSV symptoms. We hypothesize that this could be explained by sexual dysfunction associated with severe AD (25), leading to a smaller number of sexual partners. This hypothesis is, however, challenged by the opposite finding regarding the risk of condylomas.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have addressed the sexual life of patients with AD, but most of them have focused mainly on male sex ( 18 , 23 , 24 ). One Dutch study with a small sample size found that sexual satisfaction and self-perception of appearance in women with AD is significantly lower than in general populations.…”
Section: Discussionmentioning
confidence: 99%
“…In our endeavor to investigate the connection between allergic conditions and SD, several studies revealed a positive correlation between better asthma control and higher FSFI and IIEF scores, while patients with allergic rhinitis and rhinoconjunctivitis demonstrated significantly lower FSFI or IIEF scores. CSU and atopic dermatitis [96, 97] have also been associated with increased risk of SD.…”
Section: Discussionmentioning
confidence: 99%